Objective short sleep duration is associated with the activity of the hypothalamic-pituitary-adrenal axis in insomnia - Carolina D’Aurea; Dalva Poyares; Ronaldo D. Piovezan; Gisele Passos; Sergio Tufik; Marco Tulio de Mello (Arquivos de Neuro-Psiquiatria, 2015)
Objective To evaluate the association between objective short sleep duration in patients with insomnia and changes in blood parameters related to hypothalamic-pituitary-adrenal (HPA) axis activity.Method A cross-sectional pilot study was conducted in 30 middle-aged adults with chronic insomnia who were divided into 2 groups according to polysomnography (PSG) total sleep time (TST) (TST > 5h and < 5h). All patients underwent subjective analysis of sleep quality, anthropometric measurements, PSG, and determination off asting blood parameters.Results The results revealed lower sleep efficiency and higher sleep latency for those with a TST < 5h. The subjective sleep quality was worse in the TST < 5h. Significantly, higher glucose and cortisol levels were observed with a TST < 5h. Glucose, cortisol and ACTH levels were inversely correlated with the PSG total sleep time.Conclusion Patients with insomnia with objective short sleep duration had HPA-associated endocrine and metabolic imbalances chronically linked to increases in cardiovascular risk observed with this more severe insomnia phenotype.